PENINGKATAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN PENDEKATAN KONSTRUKTIVIS PADA SISWA KELAS IV SEKOLAH DASAR - Mardiah, Mardiah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study originated from the reality in schools where no maximum learning outcomes of students, because teachers teach science is a way of speaking, students do not perform learning activities often disturb her. The purpose of this study was to describe the promotion of science learning outcomes using a constructivist approach. The experiment was conducted in two cycles. The subjects were fourth grade students from elementary schools. The results of the research cycle I average 68.5. In the second cycle an increase in the average value of 79.5. Observations visible improvement in student learning outcomes in the learning process. It can be concluded in this study is to use a constructivist approach to learning science can improve student learning outcomes grade for.     Keywords:  learning automatec, constructivist approach